The Implementation of Agrarian Reform for Achieving Food Security: Lessons from West Jawa - Ida Nurlinda; Lego Karjoko; Farida Patittingi; An Nissa Ayu Mutia (Faculty of Law, Sriwijaya University, Indonesia, 2026)
Land tenure and ownership in Indonesia are marked by two interrelated structural problems: limited land availability to meet development needs and the concentration of land ownership in the hands of a small group of individuals or business entities. This concentration restricts access to land for much of the population, particularly marginal farming communities whose livelihoods depend on land cultivation. Accordingly, agrarian reform is necessary to restructure land tenure, ownership, use, and utilisation in a more equitable and sustainable manner. West Java Province, as Indonesia’s most densely populated region, faces acute challenges due to limited state land availability and a high proportion of low-income residents. In this context, agrarian reform must be treated as a development priority. This article examines agrarian reform as a regulatory and social engineering instrument aimed at achieving national development objectives, particularly food self-sufficiency and poverty alleviation, using West Java Province as a case study. The findings demonstrate that although agrarian reform in West Java has been relatively well planned and implemented, its effectiveness is constrained by insufficient budgetary support and limited involvement of Regional Government Agencies (Organisasi Perangkat Daerah/OPD), especially in the execution of access reform programmes such as economic empowerment initiatives for agrarian reform beneficiaries. The study argues that stronger institutional coordination and enhanced collaboration among OPD are essential to improve access reform and to realise food security as a central objective of agrarian reform.